Development of Realistic Mathematics Education (RME) Model Based on HOTS Problems for the Topic of Ratio - Rahmawati Rahmawati; Mayang Gadih Ranti (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2021)
Learning using Realistic Mathematics Education is a breakthrough in mathematics learning. A difficulty in implementation of PMRI on learning is there are no adequate learning resources or learning media which facilitate PMRI Implementation on learning. This research is aim to develop a PMRI learning pack on ratio topic which consist of Model Book, Teacher’s Book, Student’s Book, Lesson Plan, Worksheets and Evaluation sheets. The product was developed using Higher Order Thinking Skills (HOTS) problems to support students ability to solve problems and develop student’s thinking abillity. Development model used was Plomp Model. From research results we find that the product was valid, practice, and effective. Validation results show that the validation score was 4,19. The practically was obtained by the consistency of practically evaluation scores from expert and learning observation results. The effectiveness was obtained by four indicators, namely: 1) 80% of 35 students gain high or very high score, 2) percentage average of students and teachers activities gain ideal tolerance time, 3) 92,5 % of students give a positive response on learning, and 4) Teacher’s capability to manage to learn good category. Keywords: development, Realistic mathematics education, ratio